QT DISPERSION AND P WAVE DISPERSION IN FIBROMYALGIA - Yolbas, S.; Yildirim, A.; Duzenci, D.; Karakaya, B.; Dagli, M. N.; Koca, S. S. (Bmj Publishing Group, 2014)
[Abstract Not Available]
15th Annual European Congress of Rheumatology (EULAR) -- JUN 11-14, 2014 -- Paris, FRANCE
Keywords: Rheumatoid-Arthritis; Interval